2020
DOI: 10.1063/5.0023747
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady electro-osmotic flow of couple stress fluid in a rotating microchannel: An analytical solution

Abstract: In this work, we present the theoretical investigation of the transient rotating electro-osmotic flow of a couple stress fluid in a microchannel, through the Laplace transform technique. The analysis is dependent on the Debye–Hückel linear approximation for electrical potentials. The governing equations of the couple stress fluid are taken to address the flow field in a rotating environment. The mathematical formulation of these governing equations provides a system of ordinary differential equations, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…The symbols λ 1 and µ n f are the coefficients of viscosity. The stress tensor t ij and the deformation rate tensor d ij [54] are related by the following constitutive relation:…”
Section: Mathematical Model Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The symbols λ 1 and µ n f are the coefficients of viscosity. The stress tensor t ij and the deformation rate tensor d ij [54] are related by the following constitutive relation:…”
Section: Mathematical Model Of the Problemmentioning
confidence: 99%
“…These model relations for the incompressible fluid flow, in the absence of body force and couple stress effects [54] reduce to the following relations:…”
Section: Mathematical Model Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, external environmental effects on EOF, such as a rotating frame or peristalsis, have been considered. In microchannel flow, a rotating environment induces Coriolis force, which causes a secondary flow; this is applied in biofluid transportation, drug delivery, and DNA analysis [ 15 ]. The theoretical analysis of rotating EOF was first studied by Chang and Wang [ 16 ], and has subsequently been extended in literature [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an erect channel, mixed convection of couple stress fluid flow was considered by Mallikarjun et al 13 Their aim was achieved after finding the impact of chemical reaction on the flow. Laplace transform technique is used by Siva et al 14 to study the electro‐osmotic flow in a microchannel. The investigation found that within the electrical double layer couple stress parameter maximizes the axial flow by electro osmosis.…”
Section: Introductionmentioning
confidence: 99%